Protein components of water extracts from fruiting bodies of the reishi mushroom Ganoderma lucidum contribute to the production of functional molecules. (27th August 2018) - Kumakura, Kei; Hori, Chiaki; Matsuoka, Hiroki; Igarashi, Kiyohiko; Samejima, Masahiro
Abstract: BACKGROUND: Mushrooms have been widely considered as health foods as their extracts have anti‐hypertensive and anti‐tumor activities. After a thorough literature survey, we hypothesized that enzymes in mushroom extracts play an important role in synthesizing functional molecules. Therefore, in this study, proteins extracted from reishi mushroom ( Ganoderma lucidum ), which is used in oriental medicine, were identified by the proteomic approach, and appropriate extraction methods for improving angiotensin‐converting enzyme (ACE) inhibitory activities were investigated. RESULTS: Various glycoside hydrolases (GHs), such as β ‐ N ‐acetylhexosaminidase (GH family 20), α ‐1, 2‐mannosidase (GH family 47), endo ‐ β ‐1, 3‐glucanase (GH family 128), and β ‐1, 3‐glucanase (GH152), that degrade glycans in the fruiting body were identified. The residual glucanase activities generated β ‐oligosaccharides. Additionally, the glutamic acid protease of the peptidase G1 family was determined as the major protein in the extract, and the residual peptidase activity of the extracts was found to improve ACE inhibitory activities. Finally, it was observed that extraction at 50 °C is suitable for yielding functional molecules with high ACE inhibitory activities. CONCLUSION: Water extraction is generally believed to extract only functional macromolecules that exist in mushroom fruiting bodies. This study proposed a new concept that describes how functional molecules are produced by enzymes, including proteases and GHs, during extraction. © 2018 Society of Chemical Industry